Cost and Profitability Estimates for Producing Lychee (Litchi chinensis) in South and Central Florida - Trent Blare; Fredy H. Ballen; Nicholas Haley; Victor Contreras; Jonathan H. Crane; Daniel Carrillo (EDIS, 2022)
Florida is one of three US states (the other two being California and Hawaii) that have the climatic conditions to cultivate lychee. Given the growing consumer demand for this crop, the production of lychee has the potential to be a profitable crop for Florida growers. This publication estimates the costs and returns associated with operating a lychee grove in south and central Florida. It presents the results of field interviews with lychee growers and industry experts. Growers on average can expect to earn nearly $8,000 an acre per year from lychee production when there is a harvest, but climate variation causes inconsistent harvests. When making production decisions, growers must also consider increasing pressure from pests such as the lychee erinose mite, and strong foreign competition.